Designing Ln3+-doped BiF3 particles for luminescent primary thermometry and molecular logic - Zanella, Sofia; Trave, Enrico; Moretti, Elisa; Talon, Aldo; Back, Michele; Carlos, Luís D.; Ferreira, Rute A. S.; Brites, Carlos D. S. (Frontiers in Photonics, 2022)
The design of molecular materials suitable for disparate fields could lead to new advances in engineering applications. In this work, a series of Ln3+-doped BiF3 sub-microparticles were synthesized through microwave-assisted synthesis. The effects of doping are evaluated from the structural and morphological viewpoint. In general, increasing the Ln3+ concentration the octahedral habitus is distorted to a spheric one, and some aggregates are visible without any differences in the crystalline phase. The optical response of the samples confirms that the BiF3 materials are suitable hosts for the luminescence of the tested trivalent lanthanide (Ln3+) ions (Ln= Eu, Tb, Tm, Ho, Er, Yb). A Yb3+/Er3+ co-doped sample is presented as an illustrative example of all-photonic molecular logic operations and primary luminescent thermometry.